Stealing your life : the ultimate identity theft prevention plan - Abagnale, Frank W., 1948- (New York : Broadway Books, 2007)
Examines the growing problem of identity theft, explaining how easy it is for anyone to assume someone else's identity, the devastating impact of such a crime, ways identity thieves work, and concrete ways to protect oneself against the crime.
The sweetest con of all -- The next victim, and it's you -- The road to becoming you -- It could be public enemy number 1 or it could be grandma -- What your duplicate is doing as you -- The twenty steps to prevent identity theft -- Understanding trade lines and the meaning of R2 -- Remember that privacy statement you threw away -- My farewell to checks -- They got me, now what? -- The crime that keeps on stealing -- Write your company and congressman now! -- Staying two steps ahead (or three).
Keywords: Identity theft -- United States; Identity theft -- United States -- Prevention